PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP PEMBELIAN KEMBALI PRODUK GOSH DI KOTA PALU DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL ANTARA (STUDI PADA MAHASISWA UNIVERSITAS TADULAKO) - PUTRI, HUTHAMY MARENDA (Fakultas Ekonomi Universitas Tadulako, 2017)
This study aims to determine the effect of product quality and price on the repurchase of GOSH products in Palu City with brand trust as a variable between. Exogenous variables used in this research are Product Quality (X1) and Price (X2), while endogenous variable is Brand Trust (Y) and Repurchase (Z). This type of research is quantitative. The method of this research is descriptive causal. The samples used in this study were as many as 96 respondents with the form of sampling using the technique of Purposive Sampling. Data analysis method used in this research is the method of analysis PLS (Partial Least Square). The results of this study indicate that the price has a significant effect on brand trust (t-statistics 2,66), but the price has no significant effect on repurchase (t-statistic value 1,74). While brand trust has significant effect on repurchase (t-statistic value 7,71), likewise with product quality significantly influence brand trust (t-statistic value 4,71), but product quality has no significant effect on repurchase (value t-statistics 0.93).